A related fixed point theorem for F-contractions on two metric spaces - Olgun, Murat; Biçer, Özge; Alyıldız, Tuğçe; Altun, İshak (Hacettepe University, 2019)
Recently, Wardowski in [Fixed points of a new type of contractive mappings in complete metric spaces, Fixed Point Theory Appl. 2012] introduced the concept of F-contraction on complete metric space which is a proper generalization of Banach contraction principle. In the present paper, we proved a related fixed point theorem with F-contraction mappings on two complete metric spaces.
Keywords: Fixed Point; F-Contractions; Complete Metric Space